Edukasi tentang Keuntungan Menggunakan KB IUD di Kelurahan Bagan Pete Kota Jambi - Tuhu Perwitasari (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
AbstractThe degree of health is influenced by many factors including the environment, behavior, health services and heredity. health is a basic human right and is one of the factors that determine the quality of human resources. The use of contraception is an effort to maintain health. there are various kinds of contraception one of which is the IUD. Intrauterine device (IUD) or also called an intrauterine device (IUD) is a very effective method of contraception to prevent pregnancy reaching 99.7%. IUD birth control has many advantages including a long effective period of contraception that is 3-5 years, no hassle to remember the medication schedule, no need to change devices, or refill prescriptions and return to the doctor or midwifeto repeat contraception and most importantly the return of fertility can occur immediately after removing the IUD. These advantages make IUD birth control a pregnancy delay tool that is most effective compared to other contraceptives. the lack of mother's knowledge about the benefits of using the IUD birth control program and the large amount of incorrect information makes mothers reluctant to use the IUD birth control program. Current conditions, the use of effective long-term contraceptive methods, especially the IUD, has relatively decreased while the use of hormonal contraceptive methods dominates. the provision of information through counseling is aimed at women of childbearing age and pregnant women so that they can provide appropriate information about the benefits of using KB IUDs and the awareness of mothers to use safer contraception andlong-term. long-range